2010
DOI: 10.1002/cm.20491
|View full text |Cite
|
Sign up to set email alerts
|

Force relaxation and thin filament protein phosphorylation during acute myocardial ischemia

Abstract: Ischemia impairs myocardial function and may contribute to the progression of heart failure. In this study, rats subjected to acute ischemia demonstrated reduced Ca 2+ activated force as well as a decrease in myosin binding protein-C, titin and Ser23/24 phosphorylation of troponin I (TnI). All three proteins have been demonstrated to be downstream targets of β-adrenergic receptor activation (β-AR), leading to the hypothesis that decreased β-AR during ischemia leads to reduced protein phosphorylation and reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
2
4
0
Order By: Relevance
“…This result may not be surprising considering that previous studies have shown that myosin S1 and singleheaded myosin have different properties than even heavy meromyosin (55). In agreement with our results, the apparent rates of ADP dissociation measured from the rabbit, rat, and human myofibrils were similar to the calculated rates of ADP dissociation measured by the laser trap assay (rabbit and rat) (41,44) and from the sinusoidal length perturbation analysis of crossbridge detachment (human, rabbit, and rat) (52)(53)(54).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This result may not be surprising considering that previous studies have shown that myosin S1 and singleheaded myosin have different properties than even heavy meromyosin (55). In agreement with our results, the apparent rates of ADP dissociation measured from the rabbit, rat, and human myofibrils were similar to the calculated rates of ADP dissociation measured by the laser trap assay (rabbit and rat) (41,44) and from the sinusoidal length perturbation analysis of crossbridge detachment (human, rabbit, and rat) (52)(53)(54).…”
Section: Discussionsupporting
confidence: 81%
“…Previously, the rates of ADP dissociation from different cardiac myosins were inferred from the study of unregulated actomyosin in solution (20), laser trap experiments (44), and sinusoidal analysis on skinned cardiac muscle (52)(53)(54). The apparent rate of ADP dissociation measured by our fluorescent TnC is nearly one order of magnitude slower than that measured from actomyosin in solution for the different fast and slow myosins (20).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, approximately 40% of TnI is basally phosphorylated at both Ser-23 and 24 [9]. While TnI Ser-23/24 was previously reported to be decreased by approximately 30% in the ischemic, non-perfused rat papillary muscle [24, 25], we demonstrate ischemia increases TnI Ser-23/24 phosphorylation by 34% in the mouse left ventricular free wall containing both perfused and ischemic tissue. A limitation of this study is that we did not directly determine TnI phosphorylation in ischemic and perfused regions of the left ventricular free wall.…”
Section: Discussionsupporting
confidence: 40%
“…Protein extracts (30 μg per lane) were prepared in sample buffer (12.5% glycerol, 0.1 M Bis-Tris pH7, 1% LDS, 0.5 mmol/l EDTA, and 5 mmol/l tris(2-carboxyethyl)phosphine), resolved by 29 : 1 10% SDS-PAGE and transferred to polyvinylidene fluoride membrane as described earlier. 36 Membranes were blocked in PBS-T including 3% (w/v) BSA for 1 hour at room temperature and incubated overnight at 4 °C with a custom made, affinity purified anti-cNIS rabbit polyclonal antibody. The antibody was prepared by immunizing rabbits by DNA vaccination technology using a sequence encoding amino acids 546-642 of the canine NIS protein (GenBank XP_541946.3), and the collected serum was affinity-purified against the recombinant antigen to obtain the purified polyclonal antibody (Sdix, Newark, DE).…”
Section: Methodsmentioning
confidence: 99%